SGK1 Target Genes Involved in Heart and Blood Vessel Functions in PC12 Cells - Yu-He Li; Chia-Cheng Sun; Po-Ming Chen; Hsin-Hung Chen (Cells, 2023)
Serum and glucocorticoid-regulated kinase 1 (SGK1) is expressed in neuronal cells and involved in the pathogenesis of hypertension and metabolic syndrome, regulation of neuronal function, and depression in the brain. This study aims to identify the cellular mechanisms and signaling pathways of SGK1 in neuronal cells. In this study, the SGK1 inhibitor GSK650394 is used to suppress SGK1 expression in PC12 cells using an in vitro neuroscience research platform. Comparative transcriptomic analysis was performed to investigate the effects of SGK1 inhibition in nervous cells using mRNA sequencing (RNA-seq), differentially expressed genes (DEGs), and gene enrichment analysis. In total, 12,627 genes were identified, including 675 and 2152 DEGs at 48 and 72 h after treatment with GSK650394 in PC12 cells, respectively. Gene enrichment analysis data indicated that SGK1 inhibition-induced DEGs were enriched in 94 and 173 genes associated with vascular development and functional regulation and were validated using real-time PCR, Western blotting, and GEPIA2. Therefore, this study uses RNA-seq, DEG analysis, and GEPIA2 correlation analysis to identify positive candidate genes and signaling pathways regulated by SGK1 in rat nervous cells, which will enable further exploration of the underlying molecular signaling mechanisms of SGK1 and provide new insights into neuromodulation in cardiovascular diseases.